The thiol-reductase activity of YUCCA6 enhances nickel heavy metal stress tolerance in Arabidopsis - Cha, Joon-Yung; Jeong, Song Yi; Ahn, Gyeongik; Shin, Gyeong-Im; Ji, Myung Geun; Lee, Sang Cheol; Khakurel, Dhruba; Macoy, Donah Mary; Lee, Yong Bok; Kim, Min Gab; Lee, Sang Yeol; Yun, Dae-Jin; et al. (Frontiers in Plant Science, 2022)
Anthropogenic activities cause the leaching of heavy metals into groundwater and their accumulation in soil. Excess levels of heavy metals cause toxicity in plants, inducing the production of reactive oxygen species (ROS) and possible death caused by the resulting oxidative stress. Heavy metal stresses repress auxin biosynthesis and transport, inhibiting plant growth. Here, we investigated whether nickel (Ni) heavy metal toxicity is reduced by exogenous auxin application and whether Ni stress tolerance in Arabidopsis thaliana is mediated by the bifunctional enzyme YUCCA6 (YUC6), which functions as an auxin biosynthetic enzyme and a thiol-reductase (TR). We found that an application of up to 1 µM exogenous indole-3-acetic acid (IAA) reduces Ni stress toxicity. yuc6-1D, a dominant mutant of YUC6 with high auxin levels, was more tolerant of Ni stress than wild-type (WT) plants, despite absorbing significantly more Ni. Treatments of WT plants with YUCASIN, a specific inhibitor of YUC-mediated auxin biosynthesis, increased Ni toxicity; however yuc6-1D was not affected by YUCASIN and remained tolerant of Ni stress. This suggests that rather than the elevated IAA levels in yuc6-1D, the TR activity of YUC6 might be critical for Ni stress tolerance. The loss of TR activity in YUC6 caused by the point-mutation of Cys85 abolished the YUC6-mediated Ni stress tolerance. We also found that the Ni stress–induced ROS accumulation was inhibited in yuc6-1D plants, which consequently also showed reduced oxidative damage. An enzymatic assay and transcriptional analysis revealed that the peroxidase activity and transcription of PEROXIREDOXIN Q were enhanced by Ni stress to a greater level in yuc6-1D than in the WT. These findings imply that despite the need to maintain endogenous IAA levels for basal Ni stress tolerance, the TR activity of YUC6, not the elevated IAA levels, plays the predominant role inNi stress tolerance by lowering Ni-induced oxidative stress.